The Views of the Mufassirs About the Basics of Moral Education in Surah AL-A'raf Verses 199-202: Pandangan Para Mufassir Tentang Dasar Pendidikan AKhlak Dalam Surat AL-A'raf Ayat 199-202 - Yunia Rohmah Wijayanti; Anita Puji Astutik (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study is to determine the basis of moral education contained in the letter Al-A'raf verses 199-202. By knowing the basics of moral education, educators can be more careful in educating. In this case, the researcher provides answers to the questions: What is the opinion of the mufassir regarding the basis of moral education contained in the letter Al-A'raf verses 199-202. The type of research used by researchers is library research, for the method used is an analytical method taken from various sources of data that have been collected. This study uses a descriptive approach that is to explain the meanings contained in each verse and analyze the meaning contained in the secondary data so that the results are obtained. The results of the research findings show that the basics of moral education are: (1) forgiving, doing good and turning away from stupid people (2) holding anger and taking refuge in Allah (3) piety to Allah (4) being disobedient in error (religious value). Highlights: Forgiveness, goodness, and avoidance of ignorant people: The basis of moral education in Al-A'raf verses 199-202 emphasizes the importance of forgiving others, doing good deeds, and staying away from ignorant individuals who may lead one astray. Controlling anger and seeking refuge in Allah: Another aspect highlighted in these verses is the need to control anger and find solace in seeking refuge with Allah, emphasizing self-discipline and seeking spiritual guidance in handling emotions. Piety towards Allah and avoiding disobedience: The verses stress the significance of piety towards Allah and maintaining obedience to Him, emphasizing the religious value and the need for moral conduct based on divine guidance. Keywords: moral education, Al-A'raf verses, mufassir opinion, library research, descriptive approach